Exposure levels and health risk assessment of ambient BTX at urban and rural environments of a terai region of northern India. (November 2018) - Masih, Amit; Lall, Anurag S.; Taneja, Ajay; Singhvi, Raj
Abstract: Benzene, toluene and xylene (BTX) belong to an important group of aromatic volatile organic compounds (VOCs) that are usually emitted from various sources. BTX play a vital role in the tropospheric chemistry as well as pose health hazard to human beings. Thus, an investigation of ambient benzene, toluene and xylene (BTX) was conducted at urban and rural sites of Gorakhpur for a span of one year in order to ascertain the contamination levels. The sampling of BTX was performed by using a low-flow SKC Model 220 sampling pump equipped with activated coconut shell charcoal tubes with a flow rate of 250 ml/min for 20–24 h. The analysis was in accordance with NIOSH method 1501. The efficiency of pump was checked weekly using regulated rotameters with an accuracy of ±1%. The samples were extracted with CS2 with occasional agitation and analyzed by GC-FID. The total BTX concentration ranged from 3.4 μg m −3 to 45.4 μg m −3 with mean value 30.95 μg m −3 and median 24.8 μg m −3 . The mean concentration of total BTX was maximum during winter (39.3 μg m −3 ), followed by summer (28.4 μg m −3 ) and monsoon season (25.1 μg m −3 ). The mean concentration of BTX at urban site (11.8 μg m −3 ) was higher than that at rural site (8.8 μg m −3 ). At both the sites, T/B and X/B ratios were highest in monsoon and lowest in winters. Toluene against benzene plot shows R 2 value of 0.96 and 0.49 at urban and rural sites respectively. Higher R 2 value at urban site clearly indicates similar sources of emission for benzene and toluene. At both the sites, the estimated integrated lifetime cancer risk (ILTCR) for benzene exceeded the threshold value of 1E-06 whereas the individual hazard quotients (HQ) for BTX did not exceed unity at any of the sites. Graphical abstract: Image Highlights: An investigation of ambient BTX was conducted at urban and rural sites of Gorakhpur for a span of one year. The mean levels of B, T & X were 12.1, 22.1 and 1.3 µg m −3 at urban site whereas 7.4, 17.9 and 1.1 µg m −3 at rural site. The interspecies ratios T/B and X/B were highest in monsoon season and lowest during winters. At urban site, T vs. B plot was substantially linear. However at rural site, a considerably non-linear plot was observed. ILTCR for benzene at both the sites was higher than the threshold value 1E-06 whereas HQ for BTX did not exceed unity.